(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
The work was carried out to determine the immunogenicity of fowl cholera vaccine (FCV) produced by Livestock and Poultry Vaccine Research and Production Centre (LPVRPC) at Bangladesh Agricultural University (BAU). A total five hundred of sevenweek old Hy-sex chickens (both white and brown) were vaccinated @ 0.5 ml of 2.93×108 CFU through subcutaneous route in each selected groups such as A1, A2 and A3; and B1, B2 and B3. Booster dose was provided at 13 weeks of age in group A3 and B3. Group C was kept as unvaccinated/control. Postvaccination sera were collected at different time schedule from all the groups of birds and antibody against fowl cholera were determined by Passive haemagglutination (PHA) test. At 4 weeks of primary vaccination (11 weeks aged birds) the mean PHA titres of sera were 96.00±34.21 and 96.00±34.21in group A1 and B1 respectively. On the other hand mean PHA titres at 5-weeks following vaccination (12 weeks aged birds) were 88.00±33.12 and 96.00±34.21in group A2 and B2, respectively. After 4 weeks of booster vaccination the mean PHA titres were 104.00±33.12in A3 and 104.00±33.12 in B3 group. The mean PHA titres in chickens of unvaccinated control group C was <4±0.00.Fowl cholera vaccine prepared at LPVRPC induced a good level of immunity at the farm level and it was also demonstrated that booster (secondary) vaccination is essential to develop protective level of immunity. Res. Agric., Livest. Fish.2(1): 103-107, April 2015